PENGARUH BERBAGAI KONSENTRASI LAKTOSA DAN SARI KEDELAI PADA KUALITAS SEMEN KAMBING BOER YANG DIPRESERVASI - M.A., NOVIAN; NURSYAM, A. S.; RIYADHI, M.; RIZAL, M. (Majalah Ilmiah Peternakan, 2024)
This study aims to determine the effect of lactose and soybean milk concentrations as semen extenders for Boer goat semen. The research method employed a Completely Randomized Design (CRD), consisting of four treatments and six replications, namely: 80% lactose + 20% egg yolk as a control (P0), 97% lactose + 3% soybean milk (P1), 95% lactose + 5% soybean milk (P2), and 93% lactose + 7% soybean milk (P3). The semen samples were then stored at 3-5oC, and motility and live spermatozoa percentage were observed daily for four days. The results obtained from the research indicated that the concentration of soybean milk significantly affected (P<0.05) the motility and live spermatozoa percentage of Boer goats after cooling on the third day. The combination of 3% soybean milk with 97% lactose as an extender resulted in improved motility and live spermatozoa percentage in Boer goat semen.